Cover Image. Issue 3 (14th March 2018) - Wen, Canhong; Mehta, Chintan M.; Tan, Haizhu; Zhang, Heping
Abstract : The cover image, by Canhong Wen et al., is based on the Research Article Whole genome association study of brain‐wide imaging phenotypes: A study of the ping cohort, DOI:10.1002/gepi.22111 .